The dangerous and perishing classes - Edgar, John (Belfast Social Inquiry Society, 1852)
If children are allowed to grow up in misery, subject from the cradle to want, wretchedness, and ill usage ? if they are cut off from opportunities of learning religion ? if they hear no word of kindness, experience no sympathy ? if home and its endearments are to them unknown ? if they are accustomed to witness exhibitions of cruelty, indecency, and brutality ? what can be expected but a race of paupers and criminals? I confine myself to the perishing and dangerous classes, specially the young, and commence, by inquiring ? What is the true extent and real state of juvenile delinquency ?
A paper read before the Statistical Section of the British Association, at Belfast, September 3, 1852
Keywords: Children; Criminality; Justice; Child Poverty; 314.15